2017
DOI: 10.1007/s00231-017-2087-3
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer boundary conditions at the surface of a heated sessile droplet

Abstract: This work numerically investigates how the boundary conditions of a heated sessile water droplet should be defined in order to include effects of both ambient and internal flow. Significance of water vapor, Marangoni convection, separate simulations of the external and internal flow, and influence of contact angle throughout drying is studied. The quasisteady simulations are carried out with Computational Fluid Dynamics and conduction, natural convection and Marangoni convection are accounted for inside the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The simulations are set-up and carried out with the hybrid Finite Volume/Finite Element CFD software ANSYS CFX 15 in a similar manner as done in Ljung et al [29][30][31] for evaporating droplets. …”
Section: Methodsmentioning
confidence: 99%
“…The simulations are set-up and carried out with the hybrid Finite Volume/Finite Element CFD software ANSYS CFX 15 in a similar manner as done in Ljung et al [29][30][31] for evaporating droplets. …”
Section: Methodsmentioning
confidence: 99%
“…The evaporation of sessile droplets has been studied thoroughly both experimentally and numerically [11][12][13][14][15]. A similar setup as in the experiments performed in this study was done by Erkan and Okamoto [16] and Erkan [17], where liquid droplets were released with different impact velocities onto a dry (and later, also heated) sapphire plate.…”
Section: Introductionmentioning
confidence: 96%
“…They also found that surfactant contamination has a good performance in suppressing the Marangoni effect. Anna-Lena Ljung et al [18] adopted a numerical approach in investigating the role of boundary conditions on flow pattern both inside and outside the droplet. They found that the existence of the Marangoni effect increases the velocity within the droplet with up to three orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%